The Chinese Media Framing of the 2015’s Tianjin Explosion - Yan, Li; Lidong, Lin (Jurnal ILMU KOMUNIKASI, 2017)
This study compares the framing’s patterns of the Chinese traditional media and social media in reporting the incident of Tianjin explosion in 2015. Applying frame-building and framesetting theory, this study explores the interplay between online opinions available on Weibo and the Chinese newspapers in different phases of the crisis event. Moreover, it examines the differences in framing the incident between the state-owned party media and the commercial media. The results reveal that various frames applied by different Chinese media in reporting the incident. A complex interplay between Weibo, the Communist-owned and the commercial happened, including framebuilding, frame-setting, and frame-interacting effects.